Row gaps as drivers of economic damage in sugarcane fields - Eudocio Rafael Otavio da Silva; José Paulo Molin; Ricardo Canal Filho; Marcelo Chan Fu Wei (Biosystems Engineering, 2026)

Rapid co-sintering enables ultra-narrow pore size distribution ceria membranes for high-selectivity U(VI)/V(V) separation - Huanyu Zhou; Fan Yu; Minghui Qiu; Xiaowei Da; Xianfu Chen; Kaiyun Fu; Yiqun Fan (Chemical Engineering Journal, 2026)

Exciton regulation and directional electron transfer in artemisia-derived carbon dots/g-C3N4 heterojunction for enhanced visible-light photocatalytic antibacterial activity - Mingzhu Yuan; Weile Xie; Ran Qiu; Mingxin Zhou; Yangyang Li; Yuanxu Liu; Zibing Liu; Yupeng Yuan; Da Fu; Xiangang Lin (Chemical Engineering Journal, 2026)

Seismic-induced bearing uplift in long-span deck-type arch bridges: Analysis and mitigation under near-fault ground motions - Maojun Yuan; Lueqin Xu; Da Fu; Rui Jiang; Longhua Zeng; Jianting Zhou (Soil Dynamics and Earthquake Engineering, 2026)

An undescribed tirucallane-type triterpenoid with anti-inflammatory activity from Ailanthus altissima - Zhong-Fu Wang; Xiang Guo; Li Huang; Li-Lian Zhao; Jie Li; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2026)

Three 9-amino-1,10-anthracenedione derivatives with anti-MRSA/VRE activity from Fusarium sp. - fermented Cassia obtusifolia seeds - Zhi-Da Jin; Dai-Hua Fu; Guang-Sen Mou; Yi-Nong Wang; Xiao-Dong Luo; Hao Zhou; Shu-Kun Tang; Li-Xing Zhao (Phytochemistry, 2026)

Enhanced SMA friction self-restoring damper (eSMA-FSRD) with leveraged force-displacement control for structural seismic resilience - Maojun Yuan; Lueqin Xu; Rui Jiang; Da Fu; Wei Guo (Engineering Structures, 2026)

Exploring the therapeutic mechanism of kaempferol in acute lung injury: Network pharmacology and experimental validation - Zhu-ying Zhou; Chen-xi Zhang; Xiu-ling Wei; Chuan-fu Wu; Da-gui Chen; Fu-sheng Shang; Chun-ming Jiang (Tissue and Cell, 2026)

Cu@Ni/MoO3 core-shell catalyst for high efficiency methanolysis of hydrazine borane - Yunfeng Lei; Huilin Liu; Shunxiang Wang; Fu Ze Ho; Wen Da Oh; Yong Foo Wong; Yongjin Zou; Yong Shen Chua (Fuel, 2026)

Grazing season overrides intensity in driving plant subordinate species-mediated community dynamics across contrasting elevations of typical steppe - Yu-Wen Zhang; Lan Li; Zhao-Xia Guo; Zhao-Ling Da; Wen-Jun Wang; Xing-Qi Wang; Fu-Jiang Hou; Ji-Zhou Ren (Global and Planetary Change, 2026)

Rapid assessment of feasible flight domain for stratospheric airships under multi-physics constraints - Hailiang Wang; Ming Zhu; Da Zhao; Jiajun Ou; Dongxu Liu; Chenrui Fu (Advances in Space Research, 2026)

Investigating the mechanisms of motion response amplification for a cylindrical FPSO under wave-current coupling - Min Li; Da Li; Shenglei Fu; Yuan Zhuang; Decheng Wan (Ocean Engineering, 2026)

Bioactive edestin peptides from hemp (Cannabis sativa L.) seeds improve exercise performance under hypobaric hypoxia - Rui Zhang; Jie Liu; Liang-Liang Chen; Jia-Qi Liu; Xiao-Qian Jin; Zi-Xian Fu; Jun-Bin Xiong; Bin Jia; Jun-Ling Shi; Da-Chuan Yin (Food Research International, 2026)

Lactoferrin-derived hydrophobic peptide YIYT alleviates osteoporosis via synergistic activation of Wnt/β-catenin and BMP/Smad pathways - Zhihui Chang; Da Hong; Xiaoyu Ma; Baifeng Fu; Shuzhen Cheng; Ming Du (Food Bioscience, 2026)

Microfluidic investigation on multiphase interaction behavior and carbon dissolution sequestration mechanisms during CO₂ injection in high-water-cut deep reservoirs - Xue Zhang; Qi’an Da; Chenxi Duan; Bin Huang; Cheng Fu; Dian Zhang; Lei Li; Yuliang Su (Chemical Engineering Journal, 2026)

Quantifying soil micro-element state distribution and predicting tillage performance during sodic saline-alkali subsoiling based on mathematical model and DEM simulation approach - Min Liu; Jinchun Sun; Pinyan Lv; Dongyan Huang; Da Qiao; Yingjie Guo; Weizhi Feng; Daping Fu; Limin Jiang; Jingli Wang (Computers and Electronics in Agriculture, 2026)

A Real-World Disproportionality Analysis of Drug-Induced Heart Failure: Integrating FAERS Database and AHA Statement - Da Li; Yidan Dong; Lei Yao; Xiaozhe Chen; Yunfeng Li; Xiaohong Deng; Jianhua Li; Mingzhu Wang; Deyu Fu (Cardiovascular Toxicology, 2026)

Herbicidal activity mechanism and ecotoxicological study of novel triazolinone PPO inhibitors based on plant-derived allelochemical cinnamic acid - Li-Xia Zhao; Xian-Da Guo; Jia-Xiao Li; Yue-Li Zou; Shuang Gao; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2026)

Continuous monitoring of moisture loss of beef, beetroot, and banana slices during microwave vacuum dehydration by using THz-TDS combined with transformer-based neural network - Ying Fu; Zhihang Zhang; Da-Wen Sun (Journal of Food Engineering, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Polycrystalline ferroelectricity in a molecular crystal for piezoelectric sensing - Gele Teri; Jing-Song Tang; Peng-Cheng Zhuge; Jia-Qi Luo; Hao-Fei Ni; Lei Pan; Qiang-Qiang Jia; Yi Zhang; Da-Wei Fu; Zhi-Xu Zhang (Chemical Engineering Journal, 2026)

Metagenomic insights into species shifts and adaptation mechanisms of anammox communities treating incineration leachate - Da Kang; Yikai Zhao; Xinran Zhang; Xianyong Zeng; Xindi Fu; Bingxin Li; Zheng Ge; Liang Zhang; James P. Shapleigh; Yongzhen Peng (Chemical Engineering Journal, 2026)

Scratching the surface: The diversity and roles of triterpenoids in plant cuticular waxes - Priyanka Trivedi; Gang-Shuai Liu; Linards Klavins; Raktim Bhattacharya; Soile Jokipii-Lukkari; Adinpunya Mitra; Maris Klavins; Da-qi Fu; Laura Jaakola; Anna Szakiel; Katja Karppinen (Phytochemistry Reviews, 2026)
The cuticle and cuticular waxes play vital roles as the interface between a plant and its environment. Cuticular waxes are composed of very long-chain fatty acids (VLCFAs) and their derivatives as well as triterpenoids, which are specialized metabolites. Although triterpenoids constitute a major fraction of cuticular waxes, their functions remain poorly understood. In this review, we provide an overview of the chemical diversity of triterpenoids in the cuticular waxes of leaves and fruits of angiosperms and discuss changes in triterpenoid content during their development. The methods and challenges for the analysis of cuticular wax triterpenoids are summarized. The biosynthesis of triterpenoids is also reviewed along with recent knowledge of the potential mechanisms of triterpenoid transportation and secretion from the site of biosynthesis to the plant surface. Considering ongoing climate change, the current understanding of the effects of environmental conditions and abiotic stress factors on cuticular wax triterpenoids is reviewed. We also present an overview of the current knowledge on the roles of triterpenoids in cuticular waxes in transpiration and defense against biotic stressors and their possible role in cuticle stabilization. Moreover, owing to the generally high levels of triterpenoids in fruit cuticular waxes, the provided information on the variation and role of cuticular wax triterpenoids during postharvest fruit storage might help in the development of strategies for better fruit quality maintenance and preservation.

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

An enhanced sorting method for second-life lithium-ion batteries based on two-step clustering - Fu Wan; Yupeng Lin; Da Yang; Shufan Li; Ruiqi Liu; Lei Zhu; Wenwei Yin; Weigen Chen (Journal of Cleaner Production, 2026)

Experimental and numerical investigation on the dynamic response of a 15 MW semisubmersible floating offshore wind turbine including 1-mooring line failure scenario - Ikjae Lee; Da Li; Shenglei Fu; Cong Yi; Moohyun Kim; Alex Ran; Tuanjie Liu (Ocean Engineering, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

Sustainable recycling of spent graphite anodes: The critical role of thermal-assisted organic acid leaching in structural and performance restoration - Fu Wan; Wenwei Yin; Da Yang; Kaida Hu; Ruiqi Liu; Yupeng Lin; Weigen Chen (Journal of Environmental Chemical Engineering, 2025)

Spermidine enhances cold tolerance in tomato fruit by boosting antioxidant and energy metabolism synergy - Jian-Lin He; Shi-Yin Xie; Xiao-Dan Zhao; Da-Qi Fu (Food Research International, 2025)

Enhanced piezoelectric demulsification for high-efficiency separation of water-in-oil (W/O) emulsions based on biomimetic PVDF/liquid metal nanofiber membranes - Wen-Qiang Qiu; Jia-Qi Luo; Qing-Ke Luo; Yan-Ping Zhao; Zhi-Yu Xue; Jing-Song Tang; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Secondary natural vegetation gains in the Atlantic Forest do not offset losses of carbon stocks and conservation of priority areas - Ramon Felipe Bicudo da Silva; James D.A. Millington; Dou Yue; Maurício Humberto Vancine; Luiz Fernando Silva Magnago; Andrés Viña; Fu Bin; Margarita Huesca; Simone Aparecida Viera; Jianguo Liu (Biological Conservation, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Numerical investigation of the screen mesh effects on the heat transfer performance of wick structured heat pipe - Youyuan Fu; Da Chen; Yuxuan Cui; Shang Mao; Zilong Deng (Annals of Nuclear Energy, 2025)

Suppression of Fe loss to promote reconstructed surface via black phosphorus over NiFeB nanosheets for efficient water oxidation - Zehao Wang; Huayu Chen; Yesheng Fu; Hang Yin; Dandan Yu; Junhui Liang; Yuexiang Huang; Liuqi Wang; Wei Gao; Da Chen; Yang Hou (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Two undescribed phytoecdysteroids from Dianthus superbus L. - Yi-Han Liu; Qing Zhang; Da-Zhi Zhang; Xu-Yang Fu; Wu-Yang Liu; Jun-Mian Tian (Phytochemistry Letters, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Nitrilotriacetic acid-assisted activation of periodate by Fe(III) for organic pollutant degradation: the critical roles of high-valent iron species formation and coordination inhibition by phenolic contaminants - Xiaohui Lu; Yuantai Li; Shihuai Deng; Yanjun Li; Chenye Fu; Guochun Lv; Da Wang; Junxi Song; Hong Xiao; Jiali Peng; Bo Lai (Chemical Engineering Journal, 2025)

Seismic Data Interpolation by AVO-Preserving Hyperbolic Radon Transform Using FISTA and Polynomial Fitting - Sheng-chao Wang; Han-feng Liu; De-fu Zhang; Hui Sun; Wei Zhang; Song-da Ji (Applied Geophysics, 2025)

P16-05 The zebrafish microbiome has the capacity to bioactivate PFOS precursor compounds - S. Gutsfeld; C. Wray; N. Schweiger; A. Röhrig; H. Paschke; Q. Fu; J. Kasmanas; S. Kader; U. da Rocha; T. Tal (Toxicology Letters, 2025)

Mineralogical insights into the release behaviors of potentially toxic elements from the indigenous Zn smelting slags dumping sites - Ze-Lin Xu; Mei-Chun Zhou; Jin-Hui Miao; Wen-Chu Zhao; Rong-Bing Fu; Da-Mao Xu (Process Safety and Environmental Protection, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Functional characterization of RNAi candidate target genes in Monolepta hieroglyphica (Motschulsky) for potential pest control applications - Xu Chen; Ning Fu; Qingxuan Xu; Chun Zhang; Su Wang; Da Xiao (Journal of Asia-Pacific Entomology, 2025)

Fluorine-rich MOFs-based composite solid electrolytes realizing fast Li+ transportation kinetics and dendrite-free interface - Xiaoyang Niu; Chenjun Ju; Da Xu; Tiantian Wang; Ning Fu; Zhenglong Yang (Chemical Engineering Journal, 2025)

Dual-defect engineering strategy induced polarization loss in trimetallic MOFs/MXene-derived nanocomposites for broadening microwave absorption bandwidth - Yuanzhao Hou; Binchuan Li; Kuiren Liu; Jianshe Chen; Yongfeng Chang; Bo Wang; Shicheng Wei; Xiaocai He; Da Li; Chul B. Park; Daxue Fu; Qing Han (Chemical Engineering Journal, 2025)

Comprehensive identification of crucial biomarkers and therapeutic targets in cholestasis via integrated single-cell RNA and transcriptome sequencing analysis - Cichun Wu; Da Cheng; Juan Mo; Nianqi Zhou; Shifang Peng; Lei Fu (Mammalian Genome, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Optimizing zonal management framework suitable for mountain ecosystems by linking landscape, ecosystem service capacities and bundles nested - Yunqi Hao; Yihe Lü; Hui Dang; Da Lü; Chenjun Du; Yi Wang; Luning Wang; Xiaofeng Wang; Xuan Li; Bojie Fu (Journal of Environmental Management, 2025)

Evolution and innovation of the metazoan burrowing behaviour from Ediacaran-Cambrian transition, eastern Yunnan - Da Li; Man Li; Yongan Qi; Guochun Zhao; Jian Fu; Fuqiang Guo; Chengjun Zhang; Jianyu Guan; Shishan Zhang (Precambrian Research, 2025)

Impacts of non-thermal pretreatments on banana slices during microwave vacuum dehydration using THz-TDS and NIR-HSI techniques - Ying Fu; Yuqiao Ren; Da-Wen Sun (Journal of Food Engineering, 2025)

Binders with cationic semi-interpenetrating networks for sodium-ion batteries under extreme conditions - Chen-Hui Yang; Chi-Hon Leung; Lan-Fang Que; Fu-Da Yu; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Combined failure mechanism of tripod bucket foundations considering torsion effect - Si-Da Wu; Zhuang Jin; Yin-Fu Jin; Zhen-Yu Yin (Ocean Engineering, 2025)

SlRGLG2-SlBEL2 module regulates drought tolerance in tomato - Xiao-Lin Niu; Gang-Shuai Liu; Xiaodan Zhao; Da-Qi Fu (Plant Molecular Biology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Insights into the mechanism of ameliorative antioxidant activity and hydration characteristics in cold plasma-induced glycosylated peanut protein products - Jiao-jiao Yu; Ran-ran Zhang; Da-Qiao Yang; Xiang-na Lin; Wen-jie Fu; Yi-qi Shao; Hui Ji; Zhan-yong Guo (Food Chemistry, 2025)

Dynamic covalent synthesis of highly-crystalline and fully-cyclized aromatic COF as an artificial interphase layer toward stable lithium metal batteries - Wei Shao; Da Xu; Tiantian Wang; Huanghao Pan; Ying Liu; Xue Gao; Jiahuan Luo; Jing Wang; Zhong-Kun Li; Yao Guo; Huihui Zhao; Ning Fu; et al. (Chemical Engineering Journal, 2025)

Enhanced nonradical oxidation of thiocyanate by nano γ-Fe2O3 and Fe3C-modified 2D hierarchical porous carbon nanosheets - Yang Yang; Jianshe Chen; Daxue Fu; Yongfeng Chang; Kuiren Liu; Shuang Cui; Yina Li; Binchuan Li; Shicheng Wei; Da Li; Qing Han (Journal of Environmental Chemical Engineering, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

Ecological effect of seasonally changing temperature on the life cycle of Aurelia aurita - Da Song; Wentao Fu; Meng Fan; Kun Li (Ecological Modelling, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Quantifying supply and demand of cultural ecosystem services from a dynamic perspective - Yuxin Zhang; Bin Fu; Juying Sun; Ramon Felipe Bicudo da Silva (Land Use Policy, 2025)

Metagenomic perspectives on antibiotic resistance genes in tap water: The environmental characteristic, potential mobility and health threat - Qiyue Meng; Yibo Zhang; Da He; Yu Xia; Jie Fu; Chenyuan Dang (Journal of Environmental Sciences, 2025)

Ultrasound-Targeted β-Catenin Gene Therapy Improves the Cardiac Function in Mice After Myocardial Infarction - Lei Yang; Tong Gao; Yu Huang; Pei-he Wang; Xin-hao Han; Jie Wu; Lei Huang; Qing-en Da; Kun-fu Ouyang; Zhen Han; Hai Tian; Lu Sun (Cardiovascular Toxicology, 2025)

Autonomous net inspection and cleaning in sea-based fish farms: A review - Jiaying Fu; Da Liu; Yingchao He; Fang Cheng (Computers and Electronics in Agriculture, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Three-dimensional CSAMT Forward Modeling of Potential Landslide Sliding Surfaces Using Finite Element Method - Ruo Wang; Qingyun Di; Da Lei; Changmin Fu; Pengfei Liang; Miaoyue Wang (Applied Geophysics, 2024)

Shining light on broad-spectrum responded NaYF4:Yb,Er,Tm@Bi@BiOI: Understanding the enhanced photodegradation performance of bisphenol A and mechanisms - Jinyuan Zhang; Tian Shi; Qincan Ma; Shuang Fu; Da Cai; Fuhua Gao; Xianzhong Lin; Yueli Zhang (Journal of Environmental Management, 2024)

Improving ammonia oxidation to nitrogen across wide potential range via synergistic effect over Cu and Ni anchored Metal‐Organic Frameworks - Jiadian Chen; Huayu Chen; Zehao Wang; Yesheng Fu; Dandan Yu; Junhui Liang; Yuexiang Huang; Liuqi Wang; Ismaila Taiwo Bello; Gayi Nyongombe Ekambo; Mokhotjwa Simon Dhlamini; Da Chen (Chemical Engineering Journal, 2024)

Real-time tilapia fillet defect segmentation on edge device for robotic trimming - Yingchao He; Weidong Xu; Da Liu; Maozhen Qu; Jiaying Fu; Fang Cheng (Computers and Electronics in Agriculture, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Experimental investigation of the matching boundary and optimization strategy of a variable geometry turbocharged direct-injected hydrogen engine - Feng-yu Lai; Bai-gang Sun; Zhi-fu Zhang; Shi-wei Zhang; Kang-da Wang; Xue-ming Ju; Qing-he Luo; Ling-zhi Bao; Felix Leach (Fuel, 2024)

Self-condensation for enhancing the hydrophilicity of covalent organic polymers and photocatalytic hydrogen generation with unprecedented apparent quantum yield up to 500 nm - Islam M.A. Mekhemer; Ahmed M. Elewa; Mohamed M. Elsenety; Maha Mohamed Samy; Mohamed Gamal Mohamed; Ahmed Fouad Musa; Tse-Fu Huang; Tzu-Chien Wei; Shiao-Wei Kuo; Bo-Han Chen; Shang-Da Yang; Ho-Hsiu Chou (Chemical Engineering Journal, 2024)

Fruits’ cold tolerance: a review of mechanisms and methods - Jian-Lin He; Gang-Shuai Liu; Xiao-Dan Zhao; Lan-Ting Xiang; Shi-Yin Xie; Yun-Xiang Wang; Da-Qi Fu (Postharvest Biology and Technology, 2024)

Antibiotics ingestion altered the composition of gut microbes and affected the development and reproduction of the fall armyworm - Yan Fu; Luo-Yan Zhang; Qing-Yi Zhao; Da-Ying Fu; Hong Yu; Jin Xu; Song Yang (Journal of Pest Science, 2024)

Engineering marine phospholipid nanoliposomes via glycerol-infused proliposomes: Mechanisms, strategies, and versatile applications in scalable food-grade nanoliposome production - Dong-wen Fu; Hang Xu; Rui-qi Sun; Xue-li Liu; Zhe Ji; Da-yong Zhou; Liang Song (Food Chemistry, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Variable climatic conditions dominate decreased wetland vulnerability on the Qinghai‒Tibet Plateau: Insights from the ecosystem pattern-process-function framework - Zhengyuan Zhao; Bojie Fu; Yihe Lü; Ting Li; Lei Deng; Yuelu Wang; Da Lü; Yi Wang; Xing Wu (Journal of Cleaner Production, 2024)

Novel analysis of food processes by terahertz spectral imaging: A review of recent research findings - Ying Fu; Yuqiao Ren; Da-Wen Sun (Trends in Food Science & Technology, 2024)

The longevity evaluation of multi-metal stabilization by MgO in Pb/Zn smelter–contaminated soils - Ze-Lin Xu; Da-Mao Xu; Hai-Xuan Li; Hao-Kai Li; Rong-Bing Fu (Environmental Science and Pollution Research, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Role of probiotics/synbiotic supplementation in glycemic control: A critical umbrella review of meta-analyses of randomized controlled trials - Dengfeng Xu; Lingmeng Fu; Da Pan; YiFang Chu; Meiyuan Feng; Yifei Lu; Chao Yang; Yuanyuan Wang; Jiayue Xia; Guiju Sun (Critical Reviews in Food Science and Nutrition, 2024)

Simultaneous generation of free radicals, Fe(IV) and Fe(V) by ferrate activation: A review - Feilong Dong; Chuyun Fu; Mingbao Feng; Da Wang; Shuang Song; Cong Li; Eric Lichtfouse; Jinzhe Li; Qiufeng Lin; Virender K. Sharma (Chemical Engineering Journal, 2024)

Spatial variability mapping of indaziflam and metribuzin sorption–desorption for precision weed control - Alessandro da Costa Lima; Marcelo Chan Fu Wei; Ana Flávia Souza Laube; Ricardo Alcántara-de la Cruz; Francisco Cláudio Lopes de Freitas; Antônio Alberto da Silva; Kassio Ferreira Mendes (Precision Agriculture, 2024)

A two-stage Fe(VI) oxidation process enhances the removal of bisphenol A for potential application - Feilong Dong; Chuyun Fu; Zhu Meng; Qiufeng Lin; Jinzhe Li; Tao Zeng; Da Wang; Juntao Tang; Shuang Song (Science of The Total Environment, 2024)

How do the occurrence patterns of potentially toxic elements (PTEs) control their release behaviours from Pb/Zn smelter contaminated soils? - Da-Mao Xu; Hao-Kai Li; Ze-Lin Xu; Rong-Bing Fu (Journal of Cleaner Production, 2024)

Targeted clearance of mitochondria by an autophagy-tethering compound (ATTEC) and its potential therapeutic effects - Shuixia Tan; Da Wang; Yuhua Fu; Huiwen Zheng; Yan Liu; Boxun Lu (Science Bulletin, 2023)

Development and characterization of self-emulsifying high internal phase emulsions using endogenous phospholipids from Antarctic krill oil - Dong-wen Fu; Jing-jing Li; Dong-mei Dai; Da-yong Zhou; Bei-wei Zhu; Liang Song (Food Chemistry, 2023)

Analyzing the effects of nonthermal pretreatments on the quality of microwave vacuum dehydrated beef using terahertz time-domain spectroscopy and near-infrared hyperspectral imaging - Yuqiao Ren; Ying Fu; Da-Wen Sun (Food Chemistry, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Synthesis of flower-shaped cyclodextrin microporous organic networks for selective recovery of acetophenone and 1-phenylethanol from petrochemical effluents - Yun-Da Yue; Yu Gao; Shi-Ya Fu; Yuan-Yuan Cui; Cheng-Xiong Yang (Chemical Engineering Journal, 2023)

Piezoelectric self-power supply driven by ferroelastic host–guest supramolecule with considerable electromechanical conversion capability - Meng-Meng Lun; Jia-Qi Luo; Zhi-Xu Zhang; Jie Li; Li-Yan Xie; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2023)

DBC2 Attenuates the Stemness of CD44 Positive Gastric cancer Stem Cells by Suppressing Notch1 Signaling Pathway - Pu Xia; Da-Hua Liu; Fu Ren (Stem Cell Reviews and Reports, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The conversion of organic sulfur and strontium into inorganic compounds during the molten salt oxidation of mixed resin - Xin Liu; Yong-De Yan; Yang-Hai Zheng; Wen-Da Xu; Yun Xue; Jing-Ping Wang; Qing-Guo Zhang; Yue-Lin Wang; Fu-Qiu Ma (Journal of Environmental Chemical Engineering, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The occurrence of "yellowing" phenomenon and its main driving factors after the remediation of chromium (Cr)-contaminated soils: A literature review - Hao-Kai Li; Da-Mao Xu; Jun-Xian Wang; Ze-Lin Xu; Rong-Bing Fu (Journal of Hazardous Materials, 2023)

Experiment study on reactive powder concrete beams using spirals reinforcement under torsion - Xia Cao; Yong-peng Quan; Yi-cheng Ren; Feng Fu; Qi-zhi Jin; Da-bo He; Yan Zheng (Engineering Structures, 2023)

Systemic lupus erythematosus with high disease activity identification based on machine learning - Da-Cheng Wang; Wang-Dong Xu; Zhen Qin; Lu Fu; You-Yu Lan; Xiao-Yan Liu; An-Fang Huang (Inflammation Research, 2023)

Effect of copper ions on transformation of organic sulfur in cationic exchange resins in Li2CO3–Na2CO3–K2CO3 molten-salt system - Zhi Zhang; Yun Xue; Yue-Lin Wang; Wen-Da Xu; Yong-De Yan; Yang-Hai Zheng; Fu-Qiu Ma; Guo-Qiang Li (Chemosphere, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Multilayer nanoparticle-polymer metamaterial for radiative cooling of the stratospheric airship - Chenrui Fu; Ming Zhu; Dongxu Liu; Da Zhao; Xiaojun Zhang (Advances in Space Research, 2023)

Fe(VI) activation system mediated by a solar-driven TiO2 nanotubes electrode for CLQ degradation: Performances, mechanisms and pathways - Jinzhe Li; Chuyun Fu; Qiufeng Lin; Tao Zeng; Da Wang; Xinwen Huang; Shuang Song; Cong Li; Feilong Dong (Journal of Hazardous Materials, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Development of an Antarctic krill oil based self-microemulsion drug delivery system and its enhancement of bioaccessibility for curcumin - Dong-wen Fu; Ye Tian; Zi-han Wang; Jin-zhe Li; Da-yong Zhou; Bei-wei Zhu; Liang Song (Food Bioscience, 2023)

Lupus nephritis or not? A simple and clinically friendly machine learning pipeline to help diagnosis of lupus nephritis - Da-Cheng Wang; Wang-Dong Xu; Shen-Nan Wang; Xiang Wang; Wei Leng; Lu Fu; Xiao-Yan Liu; Zhen Qin; An-Fang Huang (Inflammation Research, 2023)

Capacitively coupled effect and capacitive decoupling of multichannel controlled-source audio magnetotellurics observations - Da Lei; Qi-hui Zhen; Ruo Wang; Chang-min Fu; Hao Ren (Applied Geophysics, 2023)

Ellagic acid induces apoptosis and autophagy in colon cancer through the AMPK/mTOR pathway - Xiong Ni; Fu-Sheng Shang; Ting-Feng Wang; De-Jun Wu; Da-Gui Chen; Biao Zhuang (Tissue and Cell, 2023)

Seasonal source identification and formation processes of marine particulate water soluble organic nitrogen over an offshore island in the East China Sea - Mengke Tian; Hao Li; Guochen Wang; Mengxin Fu; Xiaofei Qin; Da Lu; Chengfeng Liu; Yucheng Zhu; Xingzhang Luo; Congrui Deng; Sabur F. Abdullaev; Kan Huang (Science of The Total Environment, 2023)

Insights into the high performance of Co–Mn oxide supported by carbon fiber frameworks for ciprofloxacin oxidation process - Wen-Xin Fu; Meng-Zhu Qin; Huai-Yuan Niu; Qi-Yao Hu; Duan Guo; Ming-Ming Chen; Cheng-Gang Niu; Da-Wei Huang (Journal of Cleaner Production, 2023)

Egg-yolk-derived carbon dots@albumin bio-nanocomposite as multifunctional coating and its application in quality maintenance of fresh litchi fruit during storage - Xianjie Su; Hetong Lin; Bofei Fu; Shanshan Mei; Mengshi Lin; Hongbin Chen; Zongping Zheng; Hangyu Bo; Da-Peng Yang; Yifen Lin (Food Chemistry, 2023)

Correction: Identification of extracellular vesicles from J strain and wild isolate of Mycoplasma hyopneumoniae - Luiz Fernando Lino de Souza; Glaziele Campbell; Guilherme Gabriel Souza Arthuso; Natália Fialho Gonzaga; Camilla Ribeiro Alexandrino; Viviane Sisdelli Assao; Maria Aparecida Scatamburlo Moreira; Maura Da Cunha; Yung-Fu Chang; Abelardo Silva-Júnior (Brazilian Journal of Microbiology, 2023)

Catalytic ozonation for imazapic degradation over kelp-derived biochar: Promotional role of N- and S-based active sites - Da Wang; Shiwen Dong; Siqi Fu; Yi Shen; Tao Zeng; Weiti Yu; Xiaohui Lu; Lizhang Wang; Shuang Song; Jun Ma (Science of The Total Environment, 2023)

Interface engineering of hybrid ZnCo2O4@Ni2.5Mo6S6.7 structures for flexible energy storage and alkaline water splitting - Wen-Duo Yang; Rong-Da Zhao; Fang-Yu Guo; Jun Xiang; Sroeurb Loy; Liang Liu; Jia-Yu Dai; Fu-Fa Wu (Chemical Engineering Journal, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Germanium enrichment in sphalerite with acicular and euhedral textures: an example from the Zhulingou carbonate-hosted Zn(-Ge) deposit, South China - Kai Luo; Alexandre Cugerone; Mei-Fu Zhou; Jia-Xi Zhou; Guo-Tao Sun; Jing Xu; Kang-Jian He; Mao-Da Lu (Mineralium Deposita, 2022)

Epigallocatechin-3-Gallate Pretreatment Improves Autologous Adipose-derived Stem Cells Against Rheumatoid Arthritis-induced Neuroinflammation in the Brain of Collagen-induced Rats - Ming-Shan Chen; Bruce Chi-Kang Tsai; Maria Angelina Sitorus; Chia-Hua Kuo; Wei-Wen Kuo; Tung-Sheng Chen; Chien-Yao Fu; Tsung-Jung Ho; Chih-Yang Huang; Da-Tong Ju (Neurotoxicity Research, 2022)

Correction to: Microvirga puerhi sp. nov., isolated from Puerh tea garden soil - Zhi-Da Zi; Wen Wen; Fu Ma; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2022)

A typical case study from smelter–contaminated soil: new insights into the environmental availability of heavy metals using an integrated mineralogy characterization - Da-Mao Xu; Rong-Bing Fu (Environmental Science and Pollution Research, 2022)

Amplitude modulation of relative humidity by wind in Northeast China: the formation of variance annual cycle in relative humidity - Da Nian; Yu Huang; Zuntao Fu (Climate Dynamics, 2022)

Brevibacillus dissolubilis sp. nov., Isolated from Fresh Water - Wei Li; Zhao-Xuan Wang; Fu Ma; Zhi-Da Zi; Han-Yi Chen; De Zhou; Jie Lv (Current Microbiology, 2022)

Microvirga puerhi sp. nov., isolated from Puerh tea garden soil - Zhi-Da Zi; Wen Wen; Fu Ma; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2022)

Oral Enrichment of Streptococcus and its Role in Systemic Inflammation Related to Monocyte Activation in Humans with Cocaine Use Disorder - Xiaoyu Fu; Da Cheng; Zhenwu Luo; Amanda Wagner; Sylvia Fitting; Xiaomei Cong; Wanli Xu; Kendra Maas; Zhuang Wan; Jian Zhu; Zejun Zhou; William W. Stoops; et al. (Journal of Neuroimmune Pharmacology, 2022)

The changing extreme values of summer relative humidity in the Tarim Basin in northwestern China - Da Nian; Marianna Linz; Todd A. Mooring; Zuntao Fu (Climate Dynamics, 2022)

Identification of extracellular vesicles from J strain and wild isolate of Mycoplasma hyopneumoniae - Luiz Fernando Lino de Souza; Glaziele Campbell; Guilherme Gabriel Souza Arthuso; Natália Fialho Gonzaga; Camilla Ribeiro Alexandrino; Viviane Sisdelli Assao; Maria Aparecida Scatamburlo Moreira; Maura Da Cunha; Yung-Fu Chang; Abelardo Silva-Júnior (Brazilian Journal of Microbiology, 2022)

Spatially-explicit quantitative relationship for a potential PES mechanism: Cascade hydropower development in Yarlung Zangbo River Basin, China - Xiao-kang Zhu; Bin Fu; Ramon Felipe Bicudo Da Silva; Ying-man Guo; Chan-yuan Qin; Ting Feng; Hai-bing Yu; Kuang Xiao (Journal of Mountain Science, 2022)

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Discriminating hydrocarbon generation potential of coaly source rocks and their contribution: a case study from the Upper Paleozoic of Bohai Bay Basin, China - Jinjun Xu; Da Lou; Qiang Jin; Lixin Fu; Fuqi Cheng; Shuhui Zhou; Xiuhong Wang; Chao Liang; Fulai Li (Frontiers of Earth Science, 2021)

Investigation on the statistical characteristics of geoelectric field seismic anomalies in the North–South seismic belt of Chinese mainland - Hou Ze-Yu; An Zhang-Hui; Fan Ying-Ying; Tan Da-Cheng; Fu A-Long; Wei Lei (Acta Geophysica, 2021)

Summary of technology for a comprehensive geophysical exploration of gold mine in North China Craton - Qingyun Di; Guoqiang Xue; Da Lei; Qingdong Zeng; Changmin Fu; Zhiguo An (Science China Earth Sciences, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Devosia sediminis sp. nov., isolated from subterranean sediment - Fu Ma; Zhi-Da Zi; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2021)

Polymetamorphic events in the Jiao-Liao-Ji Belt, North China Craton：Evidence from integrated zircon, xenotime, and monazite LA–ICP–MS U–Pb dating - Ping-Hua Liu; Fu-Lai Liu; Zhong-Hua Tian; Da Wang; Jia Cai; Wen Zhang (International Geology Review, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Identifying the sources of seasonal predictability based on climate memory analysis and variance decomposition - Da Nian; Naiming Yuan; Kairan Ying; Ge Liu; Zuntao Fu; Yanjun Qi; Christian L. E. Franzke (Climate Dynamics, 2020)

Characteristics of the Cretaceous Magmatism in Huanghua Depression and Their Relationships with Hydrocarbon Enrichment - Fengming Jin; Jian Huang; Xiugang Pu; Changqian Ma; Lixin Fu; Chongbiao Leng; Da Lou; Mutian Qin (Journal of Earth Science, 2020)

Semi-empirical prediction method for monthly precipitation prediction based on environmental factors and comparison with stochastic and machine learning models - Huihui Zhang; Hugo A. Loáiciga; Fu Ren; Qingyun Du; Da Ha (Hydrological Sciences Journal, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Serotonin-induced miR-221/222 contribute to the activation of hepatic stellate cells - Yi Xiang; Yu-Shui Ma; Ji-Bin Liu; Zhi-Jun Wu; Xiao-Ping Wang; Li-Ping Liu; Gao-Ren Wang; Da Fu; Wei Shi (Biologia, 2020)

Karstification of Ordovician carbonate reservoirs in Huanghua depression and its control factors - Jinning Zhang; Jiansheng Zhou; Lixin Fu; Hongjun Li; Da Lou (Carbonates and Evaporites, 2020)
With extensive ancient karsts and abundant oil and gas resources, the Ordovician carbonate reservoirs in the Huanghua depression have broad prospects of exploration and development. The types, characteristics, distribution and controlling factors of karsts were investigated by means of the analysis of cores, thin slices, logging, seismic, and geochemical data in this study. The study reveals that the Ordovician carbonate reservoirs in the Huanghua depression falls into three main categories, pore type, pore-vug-fracture type and fracture type, of which, pore-vug-fracture reservoirs account for 62%. The epigenetic uniform karst mainly developed in the Late Ordovician to Early Carboniferous, while the differential karst developed in the Mesozoic. The uniform karstification mainly include chemical dissolution of the original carbonate rock, while the differential karstification not only include chemical dissolution but also hydraulic erosion and biochemical dissolution by organic acid. The burial karstification mainly involved the dissolution of the Ordovician reservoir by large amount of acidic fluids generated by the overlying Upper Paleozoic coal measure source rock while generating hydrocarbon. The dissolution caused by upwelling magmatic-tectonic hydrothermal fluids along faults also contributed to the formation of burial karst reservoirs. The sedimentation-diagenesis and paleogeomorphology-tectonic movement have certain control effects on the karstification of the Ordovician reservoirs in the Huanghua depression, determining the reservoir quality.

In Vivo Modulation of the Blood–Brain Barrier Permeability by Transcranial Direct Current Stimulation (tDCS) - Da Wi Shin; Jie Fan; Eric Luu; Wasem Khalid; Yifan Xia; Niranjan Khadka; Marom Bikson; Bingmei M. Fu (Annals of Biomedical Engineering, 2020)

Differences in root surface adsorption, root uptake, subcellular distribution, and chemical forms of Cd between low- and high-Cd-accumulating wheat cultivars - Ya-Tao Xiao; Zhen-Jie Du; Carlos-A Busso; Xue-Bin Qi; Hai-Qing Wu; Wei Guo; Da-Fu Wu (Environmental Science and Pollution Research, 2020)

Contrasting stratospheric–tropospheric multi-fractal behaviors in NAM variability - Da Nian; Zuntao Fu (Climate Dynamics, 2020)

Rare variants in FANCA induce premature ovarian insufficiency - Xi Yang; Xiaojin Zhang; Jiao Jiao; Feng Zhang; Yuncheng Pan; Qiqi Wang; Qing Chen; Baozhu Cai; Shuyan Tang; Zixue Zhou; Siyuan Chen; Hao Yin; et al. (Human Genetics, 2019)
Premature ovarian insufficiency (POI) is a major cause of reduced female fertility and affects approximately 1% women under 40 years of age. Recent advances emphasize the genetic heterogeneity of POI. Fanconi anemia (FA) genes, traditionally known for their essential roles in DNA repair and cytogenetic instability, have been demonstrated to be involved in meiosis and germ cell development. Here, we conducted whole-exome sequencing (WES) in 50 Han Chinese female patients with POI. Rare missense variants were identified in FANCA ( Fanconi anemia complementation group A ): c.1772G > A (p.R591Q) and c.3887A > G (p.E1296G). Both variants are heterozygous in the patients and very rare in the human population. In vitro functional studies further demonstrated that these two missense variants of FANCA exhibited reduced protein expression levels compared with the wild type, suggesting the partial loss of function. Moreover, mono-ubiquitination levels of FANCD2 upon mitomycin C stimulation were significantly reduced in cells overexpressing FANCA variants. Furthermore, a loss-of-function mutation of Fanca was generated in C57BL/6 mice for in vivo functional assay. Consistently, heterozygous mutated female mice ( Fanca + / − ) showed reduced fertility and declined numbers of follicles with aging when compared with the wild-type female mice. Collectively, our results suggest that heterozygous pathogenic variants in FANCA are implicated in non-syndromic POI in Han Chinese women, provide new insights into the molecular mechanisms of POI and highlight the contribution of FANCA variants in female subfertility.

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Rate Dependence of Splitting Tensile Behaviors of Sandstone and Mudstone - Jun-Jie Wang; Yu-Qiao Li; Fu-Xian Jian; Da Huang (Geotechnical and Geological Engineering, 2019)

Recent advances in the detection of 17β-estradiol in food matrices: A review - Hongbin Pu; Zhibin Huang; Da-Wen Sun; Haohua Fu (Critical Reviews in Food Science and Nutrition, 2019)

Differential temporal asymmetry among different temperature variables’ daily fluctuations - Fenghua Xie; Da Nian; Zuntao Fu (Climate Dynamics, 2019)

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Demographic expansion and genetic load of the halophyte model plant Eutrema salsugineum - Xiao‐Juan Wang; Quan‐Jun Hu; Xin‐Yi Guo; Kun Wang; Da‐Fu Ru; Dmitry A. German; Elizabeth A. Weretilnyk; Richard J. Abbott; Martin Lascoux; Jian‐quan Liu (Molecular Ecology, 2018)
The halophyte model plant Eutrema salsugineum (Brassicaceae) disjunctly occurs in temperate to subarctic Asia and North America. This vast, yet extremely discontinuous distribution constitutes an ideal system to examine long‐distance dispersal and the ensuing accumulation of deleterious mutations as expected in expanding populations of selfing plants. In this study, we resequenced individuals from 23 populations across the range of E . salsugineum . Our population genomic data indicate that E . salsugineum migrated “out of the Altai region” at least three times to colonize northern China, northeast Russia and western China. It then expanded its distribution into North America independently from northeast Russia and northern China, respectively. The species colonized northern China around 33.7 thousand years ago (kya) and underwent a considerable expansion in range size approximately 7–8 kya. The western China lineage is likely a hybrid derivative of the northern China and Altai lineages, originating approximately 25–30 kya. Deleterious alleles accumulated in a stepwise manner from (a) Altai to northern China and North America and (b) Altai to northeast Russia and North America. In summary, E . salsugineum dispersed from Asia to North America and deleterious mutations accumulated in a stepwise manner during the expansion of the species’ distribution.

In Vivo Biocompatibility and Improved Compression Strength of Reinforced Keratin/Hydroxyapatite Scaffold - Jie Fan; Meng-Yan Yu; Tong-da Lei; Yong-Heng Wang; Fu-Yuan Cao; Xiao Qin; Yong Liu (Tissue Engineering and Regenerative Medicine, 2018)

The impact of inter-annual variability of annual cycle on long-term persistence of surface air temperature in long historical records - Qimin Deng; Da Nian; Zuntao Fu (Climate Dynamics, 2018)

Understanding the triggering mechanism and possible kinematic evolution of a reactivated landslide in the Three Gorges Reservoir - Dong Ming Gu; Da Huang; Wei Dong Yang; Ji Liang Zhu; Guo Yang Fu (Landslides, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Deletion of mammalian sterile 20-like kinase 1 attenuates neuronal loss and improves locomotor function in a mouse model of spinal cord trauma - Pan-feng Wang; Da-yuan Xu; Yuntong Zhang; Xiao-bin Liu; Yan Xia; Pan-yu Zhou; Qing-ge Fu; Shuo-gui Xu (Molecular and Cellular Biochemistry, 2017)

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

Numerical Modeling of Earthquake-Induced Landslide Using an Improved Discontinuous Deformation Analysis Considering Dynamic Friction Degradation of Joints - Da Huang; Yixiang Song; Duofeng Cen; Guoyang Fu (Rock Mechanics and Rock Engineering, 2016)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Characteristics Analyses and Comparisons of the Protein Structure Networks Constructed by Different Methods - Shangli Cheng; Hua-Lin Fu; Da-Xiang Cui (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Investigation on Mechanical Behaviors of Sandstone with Two Preexisting Flaws under Triaxial Compression - Da Huang; Dongming Gu; Chao Yang; Runqiu Huang; Guoyang Fu (Rock Mechanics and Rock Engineering, 2016)

Effects of cigarette smoking and alcohol use on neurocognition and BDNF levels in a Chinese population - Xiang Yang Zhang; Yun-Long Tan; Da-Chun Chen; Shu-Ping Tan; Fu-De Yang; Giovana B. Zunta-Soares; Jair C Soares (Psychopharmacology, 2016)

Strategy to Suppress Oxidative Damage-Induced Neurotoxicity in PC12 Cells by Curcumin: the Role of ROS-Mediated DNA Damage and the MAPK and AKT Pathways - Xiao-yan Fu; Ming-feng Yang; Ming-zhi Cao; Da-wei Li; Xiao-yi Yang; Jing-yi Sun; Zong-yong Zhang; Lei-lei Mao; Shuai Zhang; Feng-ze Wang; Feng Zhang; Cun-dong Fan; et al. (Molecular Neurobiology, 2016)

Residue behavior and risk assessment of mixed formulation of imidacloprid and chlorfenapyr in chieh-qua under field conditions - Jian Xiang Huang; Cong Yun Liu; Da Hai Lu; Jia Jia Chen; Yi Cai Deng; Fu Hua Wang (Environmental Monitoring and Assessment, 2015)

Effect of β-glucan on stress tolerances and biocontrol efficacy of Cryptococcus laurentii against Penicillium expansum in pear fruit - Da Fu; Lizhen Zeng; Xiaodong Zheng; Ting Yu (BioControl, 2015)

Spectral Characteristics of Tropical Anvils Obtained by Combining TRMM Precipitation Radar with Visible and Infrared Scanner Data - Yuan-Jian Yang; Da-Ren Lu; Yun-Fei Fu; Feng-Jiao Chen; Yu Wang (Pure and Applied Geophysics, 2015)

Induction of plant virus defense response by brassinosteroids and brassinosteroid signaling in Arabidopsis thaliana - Da-Wei Zhang; Xing-Guang Deng; Fa-Qiong Fu; Hong-Hui Lin (Planta, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Positional variation in grain mineral nutrients within a rice panicle and its relation to phytic acid concentration - Da Su; Faisal Sultan; Ning-chun Zhao; Bing-ting Lei; Fu-biao Wang; Gang Pan; Fang-min Cheng (Journal of Zhejiang University-SCIENCE B, 2014)

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer - Fu-long Zhao; Yue-chao Dou; Xue-fei Wang; Da-cheng Han; Zhen-gang LV; Shuang-lei Ge; Ya-kui Zhang (Molecular Biology Reports, 2014)

Architecture and development of a multi-stage Baiyun submarine slide complex in the Pearl River Canyon, northern South China Sea - Lei Wang; Shi-Guo Wu; Qing-Ping Li; Da-Wei Wang; Shao-Ying Fu (Geo-Marine Letters, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Identification, characterization and feeding response of peptide YYb (PYYb) gene in grass carp (Ctenopharyngodon idellus) - Yong Chen; Narayan Prasad Pandit; Jianjun Fu; Da Li; Jiale Li (Fish Physiology and Biochemistry, 2014)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

Molecular characterization and expression analysis of a KIFC1-like kinesin gene in the testis of Eumeces chinensis - Jian-Rao Hu; Mei Liu; Da-Hui Wang; Yan-Jun Hu; Fu-Qing Tan; Wan-Xi Yang (Molecular Biology Reports, 2013)

Multiplex microsatellite PCR sets for parentage assignment of grass carp (Ctenopharyngodon idella) - Jianjun Fu; Yubang Shen; Xiaoyan Xu; Yong Chen; Da Li; Jiale Li (Aquaculture International, 2013)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

Yeast-Incorporated Gallium Attenuates Glucocorticoid-Induced Bone Loss in Rats by Inhibition of Bone Resorption - Zhaozhou Ren; Liqing Yang; Feng Xue; Qingjie Meng; Kejia Wang; Xian Wu; Chao Ji; Teng Jiang; Da Liu; Long Zhou; Jing Zhang; Qin Fu (Biological Trace Element Research, 2013)

SIRT1 interacts with metabolic transcriptional factors in the pancreas of insulin-resistant and calorie-restricted rats - Yong-Ru Chen; Yu-lin Lai; Shao-da Lin; Xi-tao Li; Yu-Cai Fu; Wen-Can Xu (Molecular Biology Reports, 2013)

Quantitative assessment of the effect of ABCA1 gene polymorphism on the risk of Alzheimer’s disease - Xiao-Feng Wang; Yuan-Wu Cao; Zhen-Zhou Feng; Da Fu; Yu-Shui Ma; Feng Zhang; Xiao-Xing Jiang; Yun-Chao Shao (Molecular Biology Reports, 2013)

Effect of dehydroepiandrosterone administration on recovery from mix-type exercise training-induced muscle damage - Yi-Hung Liao; Kun-Fu Liao; Chung-Lan Kao; Chung-Yu Chen; Chih-Yang Huang; Wei-Hsiang Chang; John L. Ivy; Jeffrey R. Bernard; Shin-Da Lee; Chia-Hua Kuo (European Journal of Applied Physiology, 2013)

Clinical significance of detection of antibodies to fetal and adult acetylcholine receptors in myasthenia gravis - Qi-Guang Shi; Zhi-Hong Wang; Xiao-Wei Ma; Da-Qi Zhang; Chun-Sheng Yang; Fu-Dong Shi; Li Yang (Neuroscience Bulletin, 2012)

Sprout vacuum-infiltration: a simple and efficient agroinoculation method for virus-induced gene silencing in diverse solanaceous species - Hua-xue Yan; Da-qi Fu; Ben-zhong Zhu; Hai-ping Liu; Xiao-ying Shen; Yun-bo Luo (Plant Cell Reports, 2012)

Low BDNF is associated with cognitive impairment in chronic patients with schizophrenia - Xiang Yang Zhang; Jun Liang; Da Chun Chen; Mei Hong Xiu; Fu De Yang; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2012)

Association of CTLA-4 gene polymorphisms with sporadic breast cancer risk and clinical features in Han women of Northeast China - Dalin Li; Qiujin Zhang; Fengyan Xu; Zhenkun Fu; Weiguang Yuan; Dianjun Li; Da Pang (Molecular and Cellular Biochemistry, 2012)

Molecular characterization of a KIF3A-like kinesin gene in the testis of the Chinese fire-bellied newt Cynops orientalis - Jian-Rao Hu; Na Xu; Fu-Qing Tan; Da-Hui Wang; Mei Liu; Wan-Xi Yang (Molecular Biology Reports, 2012)

The interaction between ubiquitin C-terminal hydrolase 37 and glucose-regulated protein 78 in hepatocellular carcinoma - Ying Fang; Jingui Mu; Yushui Ma; Duan Ma; Da Fu; Xizhong Shen (Molecular and Cellular Biochemistry, 2012)

Sub-chronic effect of perfluorooctanesulfonate (PFOS) on the balance of type 1 and type 2 cytokine in adult C57BL6 mice - Guang-Hui Dong; Miao-Miao Liu; Da Wang; Li Zheng; Zai-Fu Liang; Yi-He Jin (Archives of Toxicology, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Nicotine dependence and serum BDNF levels in male patients with schizophrenia - Xiang Yang Zhang; Mei Hong Xiu; Da Chun Chen; Fu De Yang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2010)

Amino Acid Homochirality may be Linked to the Origin of Phosphate-Based Life - Da Xiong Han; Hai Yan Wang; Zhi Liang Ji; An Fu Hu; Yu Fen Zhao (Journal of Molecular Evolution, 2010)

Adaptation of the externally feeding bug Elasmucha necopinata (Hemiptera: Acanthosomatidae) to its fig host - Guang-Chang Ma; Hao-Yuan Hu; Li-Ming Niu; Yue-Guan Fu; Zheng-Qiang Peng; Wen-Jun Bu; Da-Wei Huang (Symbiosis, 2009)

Gadolinium promoted proliferation and enhanced survival in human cervical carcinoma cells - Ying Zhang; Li-Juan Fu; Jin-Xia Li; Xiao-Gai Yang; Xiao-Da Yang; Kui Wang (BioMetals, 2009)

Overexpression of CyclinD1 and underexpression of p16 correlate with lymph node metastases in laryngeal squamous cell carcinoma in Chinese patients - Zhi-jie Fu; Zhi-yong Ma; Qi-rong Wang; Da-peng Lei; Rong Wang; Chun-xi Liu; Xin-liang Pan (Clinical & Experimental Metastasis, 2008)

Ischemic preconditioning induces chaperone hsp70 expression and inhibits protein aggregation in the CA1 neurons of rats - Peng-Fei Ge; Tian-Fei Luo; Ji-Zhou Zhang; Da-Wei Chen; Yong-Xin Luan; Shuang-Lin Fu (Neuroscience Bulletin, 2008)

Vanadyl bisacetylacetonate induced G1/S cell cycle arrest via high-intensity ERK phosphorylation in HepG2 cells - Ying Fu; Qin Wang; Xiao-Gai Yang; Xiao-Da Yang; Kui Wang (JBIC Journal of Biological Inorganic Chemistry, 2008)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Assignment of CCR7 gene to chicken chromosome 27 by radiation hybrid panel mapping - Yong Tian; Li-zhi Lu; Yan Fu; Zheng-rong Tao; Jun-da Shen; De-qian Wang; Ai-ping Yuan; Zhao-zheng Yin (Journal of Zhejiang University-SCIENCE B, 2007)

Identification and genetic relationships of kenaf (Hibiscus cannabinus L.) germplasm revealed by AFLP analysis - Zhou Cheng; Bao-Rong Lu; Kazuhiko Sameshima; Da-Xu Fu; Jia-Kuan Chen (Genetic Resources and Crop Evolution, 2004)

Role of tumor metastasis suppressor gene KAI1 in digestive tract carcinomas and cancer cells - Qiao Wu; Yuan Ji; Ming-qing Zhang; Yu-qiang Chen; Fu Chen; Da-lin Shi; Zong-hui Zheng; Yao-jian Huang; Wen-jin Su (Cell and Tissue Research, 2003)